The 'Casas GEO' movement an ethnogrpahy of a new housing experience in Cuernavaca, Mexico - Inclán Valadez, María Cristina (Premio Internacional de Tesis de Investigación sobre Vivienda y Desarrollo Sustentable 2014, 2013)
First, it conceptualises the housing project as a mutable place, produced through daily interaction and a variedcoexistence. Second, it understands the residential space as the arena for the emergence of a new cultural category created in everyday life through specific claims, values and symbols expressed in the urban landscape. The thesis shows how the developer, the GEO company, attempted to construct a set of individual values and codes of behaviour for residents, as an imperative to make the site liveable. But, it considers also how residents use their houses differently from the developersf intentions through strategies of re]appropriation and personalisation in order to communicate ideas of distinction and egoodf taste. Importantly, residents had to deal with a range of inconsistencies, flaws and drawbacks in the projectfs realisation that challenged representations of the egoodf city, social progress and modernity. The esearch shows how these failings influence peoplefs lives, especially their aspirations and sense of identity.My claim is that in the making of the Casas GEO movement people negotiate a culturalformation and produce a new space that allows ways of imagining, aspiring to, andmodes for taking part in a modern eurbanf life. Yet, the making of the movement alsoexposes the fragility of a housing project that claims to be the formula for upwardmobility of lower]income groups in Mexico.